Natural flowering control of pineapple ‘Pérola’ and ‘Vitória’ using aviglycine hydrochloride - Pires, Andrea; Silva, Laís Fontana; Ferreira, Thayanne Rangel; Crasque, Jeane; Neto, Basílio Cerri; Arantes, Lúcio de Oliveira; Schmildt, Edilson Romais; Ventura, José Aires; Oliveira, Vinicius de Souza; Dousseau-Arantes, Sara (Frontiers in Plant Science, 2025)
IntroductionAviglycine hydrochloride (Aminoethoxyvinylglycine (AVG)) is an ethylene synthesis inhibitor recommended worldwide for controlling natural flowering of pineapple plants. However, the recommended dose depends on the environment, genotype and age of the plant. The objective was to evaluate the effect of AVG concentration in three application periods for controlling flowering in ‘Pérola’ (susceptible to fusariosis) and ‘Vitória’ (resistant to fusariosis) pineapple plants.MethodsThe study was conducted in the field in the municipality of Sooretama, Espírito Santo-ES, Brazil. The experimental design used was randomized blocks in a 3×3+1 factorial scheme, consisting of three concentrations (100, 200 and 400 mg L-1) and three application times (April–July, May–July and June–July), with four replicates. The control was the plants without application. Flowering, phytotoxicity, morphological characteristics of plants, photosynthetic pigments, carbohydrate allocation and physical-chemical characteristics of fruits were evaluated.ResultsAVG controlled natural flowering in both pineapple cultivars and the effect was proportional to the increase in concentration. Increasing the concentration and number of applications induced phytotoxic effects and reductions in starch and photosynthetic pigment contents in the leaves, also reducing vegetative development and fruit weight. The cultivar Pérola was more susceptible to natural flowering control, with a longer period of floral inhibition and reduction in vegetative and reproductive development when 400 mg L-1 was applied.DiscussionTherefore, we recommend that AVG be applied at a concentration of 100 mg L-1 before the climatic conditions for natural floral induction occur, which in the case of the northern coast of Espírito Santo, Brazil, occurs between June and July, and can extend until August, if nighttime temperatures are below 20 °C, being responsible for controlling natural flowering by 80%.